Dual role of USP30 in controlling basal pexophagy and mitophagy - Marcassa, Elena; Kallinos, Andreas; Jardine, Jane; Rusilowicz-Jones, Emma V; Martinez, Aitor; Kühl, Sandra; Islinger, Markus; Clague, Michael J; Urbé, Sylvie (EMBO reports, 2018)
Abstract USP30 is an integral protein of the outer mitochondrial membrane that counteracts PINK1 and Parkin-dependent mitophagy following acute mitochondrial depolarisation. Here, we use two distinct mitophagy reporter systems to reveal tonic suppression by USP30, of a PINK1-dependent component of basal mitophagy in cells lacking detectable Parkin. We propose that USP30 acts upstream of PINK1 through modulation of PINK1-substrate availability and thereby determines the potential for mitophagy initiation. We further show that a fraction of endogenous USP30 is independently targeted to peroxisomes where it regulates basal pexophagy in a PINK1- and Parkin-independent manner. Thus, we reveal a critical role of USP30 in the clearance of the two major sources of ROS in mammalian cells and in the regulation of both a PINK1-dependent and a PINK1-independent selective autophagy pathway.
Gesehen am 11.10.2019